The Influence of Adaptive Organizational ‎Climate and DigitalTechnology Utilization on ‎Employee MotivationOf Local Startups in ‎Gorontalo - Yantu, Irwan; Mendo, Andi Yusniar; Biki, Syamsul B. (International Journal of Accounting and Economics Studies, 2026)
The development of digital technology and disruption of business innovation has affected various factors, including ‎startups. The development of startups in Indonesia is currently quite rapid. At present, there are more than 1,500 local ‎startups in Indonesia. A startup, as a dynamic and innovation-based business entity, requires an organizational structure that is ‎flexible, adaptive, and makes optimal use of digital technology. The urgency of this research is that, first, Startups have great ‎potential in driving the local economy in Gorontalo through innovation. Second, the startup work environment is often ‎dynamic, full of uncertainty, and requires rapid adaptation. Third, the potential synergy of adaptive organizational climate ‎and digital technology is likely to interact with the effective use of digital technology. The research objective is to determine ‎the effect of adaptive organizational climate and digital technology utilization on the work motivation of startup employees in ‎Gorontalo, both partially and simultaneously. The research method used is a quantitative approach with an exploratory type ‎of research, with SEM-PLS analysis. The expected results are, first, an overview of the influence of an adaptive ‎organizational climate, the use of digital technology, and employee work motivation at startups in Gorontalo. Second, the ‎influence of organizational climate on employee work motivation is proven. Startups with a more adaptive climate are ‎expected to have employees with higher work motivation. Third, the effect of digital technology utilization on employee ‎work motivation is proven, with effective technology utilization expected to increase efficiency, collaboration, and ultimately ‎work motivation. Fourth, the joint effect of adaptive organizational climate and digital technology utilization on employee ‎work motivation is proven. The combination of the two is expected to have a greater impact on work motivation. The ‎results of hypothesis testing show that the utilization of digital technology has a positive and significant influence on ‎employee work motivation (sig = 0.000
Keywords: Organizational climate; Adaptive; Digital technology; Work motivation; Startup